Discussion on the application of ISBAR standard procedure of Traditional Chinese Medicine (ISBAR中医标准化流程的应用实践) - YIN Kexin (尹可欣); XING Hui (兴慧); HU Shirong (胡世荣); WANG Huaxin (王华新); TANG Ling (唐玲) (Journal of International Translational Medicine Limited, 2022)
This paper summarized the clinical application of Identification-Situation-Background-Assessment-Recommendation(ISBAR) standardized Traditional Chinese Medicine (TCM) nursing process, and discussed the importance of effective communication ability for TCM nursing safety under the current medical model and new medical reform. ISBAR is applied to nursing shift, transfer of patients between departments, integrated ward round of medical care, nursing clinical teaching and other links, so as to form a standardized process. The goal of standardized process based on ISBAR is to improve of the quality of TCM nursing work, reduce the occurrence of clinical nursing risk events, improve the standardization, homogeneity, refinement of TCM nursing work and provide reference and suggestions for professional development of TCM nursing. (本文通过对ISBAR中医护理标准化流程临床应用进行总结, 分析在当前医学模式、新医改下有效沟通能力对中医护理安全的重要性, 将ISBAR与中医结合应用到护理交接班、科室间转运患者、医护一体化查房、护理临床教学等各个环节, 使之形成标准化流程, 让中医临床护理工作有章可循, 有规可依, 在减少临床护理风险事件发生的同时促进中医护理工作质量的提升, 让中医护理工作向标准化、同质化、精细化、延续化方向发展, 以此为中医护理专业化发展提供借鉴和思考。)